2021
DOI: 10.1111/kykl.12285
|View full text |Cite
|
Sign up to set email alerts
|

Financial stress and economic growth: The moderating role of trust

Abstract: The literature suggests that trust can influence the behavior of economic agents and improve access to financing for both households and corporations. Subsequently, this might have implications for the consumption of households and the investments of corporations. Therefore, trust could mitigate the negative impact of financial stress on economic growth. To test this hypothesis, we use a sample of EU countries over the period 2002-2020 and examine the interaction of trust with financial stress in shaping GDP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 130 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…Alexiou et al (2018) found that over the period 1998-2014, increased credit flows negatively affected 34 European and Commonwealth of Independent States economies while the significant positive effect of money supply on growth before the GFC is not confirmed for advanced economies in contrast to developing countries. Makrychoriti et al (2022) used a sample of EU countries over the period 2002-2020 and suggested that trust can influence the behaviour of economic agents and improve access to financing for both households and corporations. Therefore, trust could mitigate the negative impact of financial stress on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alexiou et al (2018) found that over the period 1998-2014, increased credit flows negatively affected 34 European and Commonwealth of Independent States economies while the significant positive effect of money supply on growth before the GFC is not confirmed for advanced economies in contrast to developing countries. Makrychoriti et al (2022) used a sample of EU countries over the period 2002-2020 and suggested that trust can influence the behaviour of economic agents and improve access to financing for both households and corporations. Therefore, trust could mitigate the negative impact of financial stress on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, their empirical strategy fails because it is unlikely to incorporate all possible causal growth determinants in their reduced form—unlike a macroeconomic growth model. Makrychoriti et al (2021) also skipped the theoretical modeling phase when they found that trust moderates the association between financial stress and economic growth. Unfortunately, they did not test the Zak and Knack (2001) model, so their finding is not useful to uncovering whether there is empirical evidence of a causal trust‐growth relationship.…”
Section: The Five Deadly Sins Of the Trust Literaturementioning
confidence: 99%